Analysis of the Effectiveness of the Plyometric Training Method in Improving Sprint Athletes’ Performance - Irfan, Irfan (Champions: Education Journal of Sport, Health, and Recreation, 2025)
This study aims to explore and understand the experiences and perceptions of sprint athletes at SMA Negeri 1 Kota Tanjungbalai regarding the implementation of plyometric training methods to improve their performance. A qualitative approach with a case study method was employed, involving 10 sprint athletes from the school’s athletics extracurricular program who had participated in plyometric training for at least three months. Data were collected through in-depth interviews, participatory observation, and training documentation. Data analysis was conducted using thematic coding techniques to identify patterns and meanings in the athletes’ experiences during plyometric training. The results indicate that athletes experienced significant improvements in speed, explosive strength, and mental readiness during competitions after regularly undergoing plyometric training. Additionally, motivation and training discipline increased because the method was considered challenging and varied. However, some athletes expressed concerns about injury risks if training techniques were not performed correctly. This study emphasizes the importance of a holistic training approach and professional supervision in implementing plyometric training to optimally enhance sprint athletes’ performance.